2022
DOI: 10.1101/2022.02.05.479242
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pharmacogenetic and whole-brain activity analyses uncover integration of distinct molecular and circuit programs that drive learning

Abstract: Habituation is a foundational learning process critical for animals to adapt their behavior to changes in their sensory environment. Although habituation is considered a simple form of learning, the identification of a multitude of molecular pathways including several neurotransmitter systems that regulate this process suggests an unexpected level of complexity. How the vertebrate brain integrates these various pathways to accomplish habituation learning, whether they act independently or intersect with one an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Multiple mechanisms of C-start habituation have also been discovered (Wolman et al, 2011;Corradi and Filosa, 2021;Nelson et al, 2022). For example, the persistent form of habituation response in zebrafish that lasts 25 min to 1 h could be inhibited by N-methyl-D-aspartate receptors (NMDAR) antagonists (Roberts et al, 2011).…”
Section: Startle Responsivenessmentioning
confidence: 99%
“…Multiple mechanisms of C-start habituation have also been discovered (Wolman et al, 2011;Corradi and Filosa, 2021;Nelson et al, 2022). For example, the persistent form of habituation response in zebrafish that lasts 25 min to 1 h could be inhibited by N-methyl-D-aspartate receptors (NMDAR) antagonists (Roberts et al, 2011).…”
Section: Startle Responsivenessmentioning
confidence: 99%
“…Recently, we found that long-term habituation of the response of larval zebrafish to sudden pulses of whole-field darkness, or dark flashes (DFs), involves multiple molecularly independent plasticity processes that act to suppress different components of the behavioural response (Randlett et al, 2019). Similar behavioural, pharmacological, and genetic experiments have led to comparable conclusions in acoustic short-term habituation (Nelson et al, 2022), and habituation in C. elegans (McDiarmid et al, 2019a,b), indicating that habituation generally acts via multiple modular plasticity processes. These modules act to mute or shift behavioural responses to repeated stimuli.…”
Section: Introductionmentioning
confidence: 95%